Pengembangan Desain Instructional Mata Kuliah Bahasa Inggris Berbasis English for Specific Purposes - Yusniarti Runggo; Hendriyani (Universitas Tadulako, 2021)
English for Specific Purposes (ESP) is an English learning approach where the topics and methods used in learning are made based on the needs of learning English. This study aims to develop based teaching materials English for Specific Purposes appropriate to student needs. The need for learning English was identified using the questionnaire obtained from students of the Agricultural Products Processing Technology study program as research subjects. Data were analyzed using descriptive techniques in the numbers and percentages. The result showed that the needs of the students for the ESP English course are very diverse, it can be concluded that English is not only for their current needs but also for future work purposes.